PENGARUH PEMANFAATAN CHATGPT DALAM MODEL PEMBELAJARAN PROBLEM-BASED LEARNING TERHADAP HASIL BELAJAR SISWA KELAS X SMK NEGERI 1 MEDAN - Siti Nurkhalifah; Rotua Sahat Pardamean Simanullang (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the low learning outcomes of students in the subjects of Job/Professional Profiles and Business Opportunities in the Field of Office Management and Business Services at SMK Negeri 1 Medan, as well as the limited use of artificial intelligence technology in the learning process. The purpose of this study was to determine the effect of ChatGPT utilization in the Problem-Based Learning (PBL) model on the learning outcomes of tenth-grade students. The method used was quantitative research with a quasi-experimental design, involving two classes: X MPLB 2 as the experimental group using ChatGPT-assisted PBL, and X MPLB 3 as the control group using conventional PBL. Data were obtained through pretest and posttest analyses using normality, homogeneity, t-test, and N-Gain tests. The results showed that the average posttest score of the experimental group was 89.26 with an N-Gain of 0.83 (high and effective category), while the control group scored 79.89 with an N-Gain of 0.67 (moderately effective category). Hypothesis testing showed a significant effect of ChatGPT utilization on improving student learning outcomes. Thus, the integration of ChatGPT in PBL was proven to increase learning effectiveness and help students develop critical thinking and problem-solving skills relevant to the digital workplace.